Wavelength dependent luminescence decay kinetics in `quantum-confined' g-C(3)N(4)nanosheets exhibiting high photocatalytic efficiency upon plasmonic coupling - Mondal, Sanjit; Sahoo, Lipipuspa; Vaishnav, Yuvraj; Mishra, Samita; Roy, Raj Sekhar; Vinod, C. P.; De, Arijit K.; Gautam, Ujjal K. (Journal of Materials Chemistry A, 2020)
Serendipitous observations offer newer insights into materials properties. Here we describe g-C(3)N(4)nanosheets exhibiting remarkably blue-shifted photoluminescence within the 390-580 nm range centred at 425 nm which matches more closely with its `quantum-dots', and yet is excitation-wavelength independent. Moreover, surprisingly, the luminescence decay becomes increasingly slow at higher emission wavelengths, by up to 10 times. The nanosheets absorb only a fraction of visible-light. To improve this, when we designed a nanocomposite of g-C(3)N(4)and Au nanoparticles (NPs), it retained the PL characteristics and also exhibited excellent light-harvesting and photocatalytic efficiency for benzylamine (BA) oxidation. The surface plasmon resonance of the Au NPs is responsible for the high visible-light response and assisting the reaction by the `hot-electron' injection mechanism, while an uncharacteristic, pronounced co-catalytic effect by them further improves the efficiency. The conversion is 98% with >99% selectivity over 1.5 h of natural sunlight and open-air, probably the highest efficiency for BA photo-oxidation reactions. Even though such a dual role by plasmonic NPs has remained unscrutinized, we argue that the charge-transfer processes for the `hot-carrier' injection and co-catalytic events are well-separated in time due to a much slower photon incident frequency on a catalyst particle, enabling both to occur simultaneously in the same particle.

Enhancing the Catalytic Activity of Pd Nanocrystals towards Suzuki Cross-Coupling by g-C3N4 Photosensitization - Mondal, Sanjit; Sahoo, Lipipuspa; Banoo, Maqsuma; Vaishnav, Yuvraj; Prabhakaran Vinod, Chathakudath; Gautam, Ujjal (Chemnanomat, 2024)
Developing renewable means of activating molecules over traditional catalysts for C-C bond formation is desirable for industrial applications. Herein, we report a strategy to improve the efficiency of Pd nanoparticles (NPs) for the Suzuki cross-coupling reactions by visible-light irradiation using g-C3N4 nanosheets (NSs) as photosensitizer. Pd NPs mounted on g-C3N4 become electron-rich under visible-light due to generation of excited electrons in g-C3N4 and thereby accelerate the rate-determining step. Remarkable photocatalytic activity was accomplished utilizing Pd/g-C3N4 for the Suzuki cross-coupling reaction in environmentally benign aqueous settings under room temperature conditions. The activity remarkably improves (similar to 2.5 times) upon light irradiation, yielding one of the highest known turnover frequencies (TOF) of 1858 h(-1) and confirming the photosensitizer role of g-C3N4. The TOF for coupling of aryl bromides is also significantly high (similar to 356 h(-1)). We establish that the low-energy/long-lived excitons preferencially transfer to Pd, paving a way for rational designing photocatalysts for various C-C coupling reactions.
Keywords: 2D graphitic carbon nitride; C-C cross-coupling; exciton transfer; heterogeneous photocatalyst; Photosensitization